Tetrahedral amorphous carbon prepared filter cathodic vacuum arc for hole transport layers in perovskite solar cells and quantum dots LEDs. Issue 1 (31st December 2019) - Seok, Hae-Jun; Kang, Yong-Jin; Kim, Jongkuk; Kim, Do-Hyeong; Heo, Su Been; Kang, Seong Jun; Kim, Han-Ki
ABSTRACT: (ta-C) films coated through the filtered cathodic vacuum arc (FCVA) process as a hole transport layer (HTL) for perovskite solar cells (PSCs) and quantum dot light-emitting diodes (QDLEDs). The p-type ta-C film has several remarkable features, including ease of fabrication without the need for thermal annealing, reasonable electrical conductivity, optical transmittance, and a high work function. X-ray photoelectron spectroscopy and ultraviolet photoelectron spectroscopy examinations show that the electrical properties (sp 3 /sp 2 hybridized bond) and work function of the ta-C HTL are appropriate for PSCs and QDLEDs. In addition, in order to correlate the performance of the devices, the optical, surface morphological, and structural properties of the FCVA-grown ta-C films with different thicknesses (5 ~ 20 nm) deposited on the ITO anode are investigated in detail. The optimized ta-C film with a thickness of 5 nm deposited on the ITO anode had a sheet resistance of 10.33 Ω −2, a resistivity of 1.34 × 10 −4 Ω cm, and an optical transmittance of 88.97%. Compared to the reference PSC with p-NiO HTL, the PSC with 5 nm thick ta-C HTL yielded a higher power conversion efficiency (PCE, 10.53%) due to its improved fill factor. Further, the performance of QDLEDs with 5 nm thick ta-C hole injection layers (HIL) showed better than the performance of QDLEDs with different ta-C thicknesses. It is concluded that ta-C films have the potential to serve as HTL and HIL in next-generation PSCs and QDLEDs. Graphical abstract: uf0001